Humor and satire on the hunt based on “Łowiec Polski”, “Łowiec Wielkoposki” and landed gentry archives - Studnicka-Mariańczyk, Karolina; Hubicki, Piotr (Laughter, humour, satire, 2024)
Hunting has accompanied man since the dawn of time. The history of hunting is directly intertwined with the history of society. As society changed, the social aspect of hunting developed. This article deals with the second half of the 19th century; its aim is to show hunting humour and satire. It has been developed on the basis of the archives of the landed gentry, the stories, poems and rhymes related to hunting contained in them. Another source of hunting humour and satire are magazines describing rural culture and hunting, which were very popular at the time. Funny stories were published in the magazines “Wieś i Dwór”, “Wieś Ilustrowana” and in the pages of “Łowca Polski”. The authors’ aim in this article is to show and discuss the characteristic hunting humour of the second half of the 19th century.